The Effect of User Experience (UX) and E-Service Quality (ESQ) on CustomerLoyalty Through Customer Satisfaction as a Mediating Variable(A Study of Gen-Z Users of the McDonald’s App) - Mar Atussha Lihah; Rosyid Nurrohmanr (JURNAL COMPUTECH & BISNIS, 2026)
This study seeks to investigate the impact of user experience on customer satisfaction, the effect of e-service quality on customer satisfaction, the relationship between user experience and customer loyalty, the influence of e-service quality on customer loyalty, and the effect of customer satisfaction on customer loyalty among Gen-Z users of the McDonald's app. This study utilizes the Stimulus-Organism-Response (SOR) theory and the Expectation Disconfirmation Theory (EDT) to elucidate how external stimuli, such as user experience and e-service quality, affect users' internal assessments and behavioral responses. The research strategy utilized is a correlational study using a quantitative methodology, and hypothesis testing was performed using a Structural Equation Model (SEM) based on Partial Least Squares (PLS). The sample consisted of 120 respondents who are current users of the McDonald's app in Indonesia, chosen through unintentional sampling. The study's results indicate that service experience positively and significantly influences customer satisfaction; e-service quality positively and significantly affects customer satisfaction; user experience positively and significantly impacts customer loyalty; and e-service quality positively and significantly influences customer loyalty. Moreover, customer satisfaction exerts a positive and substantial influence on customer loyalty and serves as a mediating variable in the relationship between user experience and e-service quality.